2010
DOI: 10.1007/s11605-009-1139-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track Surgery Improves Postoperative Recovery in Patients with Gastric Cancer: A Randomized Comparison with Conventional Postoperative Care

Abstract: Fast-track surgery can lessen postoperative stress reactions and accelerate rehabilitation for patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
190
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(210 citation statements)
references
References 38 publications
11
190
2
4
Order By: Relevance
“…In their study, no differences were found with respect to postoperative morbidity and mortality, but the recovery of bowel function was significantly improved in the early diet group. In addition, in one study about ''fast-track surgery'' in patients with gastric cancer, Wang et al [28] introduced oral nutrition on the first postoperative day and found that hospital stays and medical costs were reduced and quality of life was improved. Unlike the study by Wang et al, the present study more specifically focused on the early oral feeding after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, no differences were found with respect to postoperative morbidity and mortality, but the recovery of bowel function was significantly improved in the early diet group. In addition, in one study about ''fast-track surgery'' in patients with gastric cancer, Wang et al [28] introduced oral nutrition on the first postoperative day and found that hospital stays and medical costs were reduced and quality of life was improved. Unlike the study by Wang et al, the present study more specifically focused on the early oral feeding after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [15] reported that the first day of flatus after gastric surgery was earlier in patients who received fast-track surgery care than in those who received conventional care (3 vs. 4 days). Teeuwen et al [5] found that oral intake in their ERAS group was higher than that in the conventional group after colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because laboratory testing was performed on POD 7 in both groups, the mean day of discharge did not differ significantly. Wang et al [15] reported that the postoperative hospital stay after gastric surgery was shorter in patients who received fast-track surgery care than in those who received conventional care.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized comparison between fast-track surgery and conventional care in gastric cancer patients (n = 45 and n = 47 respectively) showed less stress response in the fast-track surgery group [105] . This was measured by serum tumor necrosis factor-alfa, CRP and interleukin-6 levels.…”
Section: Advances In Postoperative Carementioning
confidence: 98%